2015
DOI: 10.1097/01.mpg.0000472211.46517.33
|View full text |Cite
|
Sign up to set email alerts
|

Op‐7 Therapeutic Effects of Domperidone on Abdominal Pain‐predominant Functional Gastrointestinal Disorders

Abstract: Background: Impaired gut barrier function has been reported in some functional gastrointestinal (GI) disorders. Evidences suggest that gut microbiota affects GI motility in particular Lactobacillus species elicits anti-inflammatory activity and exerts protective effects on damage induced by pathogen Gram negative-derived lipopolysaccharide (LPS). LPS produced an oxidative imbalance in human colonic smooth muscle cells (SMC) that persists after LPS-washout and contributes to SMC morphofunctional alterations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Single studies assessed the effectiveness of 8 different pharmacological agents compared to usual care or placebo: the anti-muscarinic drug trimebutine (53), the 5-HT 4 (5-hydroxytryptamine) agonist tegaserod (54), the antihistamine cyproheptadine (55), the serotonin agonist pizotifen (56), the selective serotonin reuptake inhibitor citalopram (57), the hormone melatonin (58), the dopamine receptor agonist domperidone (59), and the H2 receptor agonist famotidine (60). Four studies reported significant reductions in pain (53)(54)(55)(56), 2 reported mixed findings (59,60), and 3 no effect on pain outcomes (57,58). Small sample sizes, poor reporting, and a lack of recognised pain outcome measures meant there was insufficient evidence of effectiveness for these single studies of pharmacological intervention.…”
Section: Effects Of Other Pharmacological Interventions: 8 Single Stu...mentioning
confidence: 99%
“…Single studies assessed the effectiveness of 8 different pharmacological agents compared to usual care or placebo: the anti-muscarinic drug trimebutine (53), the 5-HT 4 (5-hydroxytryptamine) agonist tegaserod (54), the antihistamine cyproheptadine (55), the serotonin agonist pizotifen (56), the selective serotonin reuptake inhibitor citalopram (57), the hormone melatonin (58), the dopamine receptor agonist domperidone (59), and the H2 receptor agonist famotidine (60). Four studies reported significant reductions in pain (53)(54)(55)(56), 2 reported mixed findings (59,60), and 3 no effect on pain outcomes (57,58). Small sample sizes, poor reporting, and a lack of recognised pain outcome measures meant there was insufficient evidence of effectiveness for these single studies of pharmacological intervention.…”
Section: Effects Of Other Pharmacological Interventions: 8 Single Stu...mentioning
confidence: 99%